Model Persediaan Pemasok-Pembeli Dengan Produk Cacat Dan Kecepatan Produksi Terkontrol. - Sejati, Nelita Putri; Jauhari, Wakhid Ahmad; Rosyidi, Cucuk Nur (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
In this paper, we consider a joint economic lot size (JELS) model consisting of single vendor single buyerwith single product. We intend to study the impact of defective items and controllable production rate onthe model. The demand in buyer side is assumed to be stochastic. The delivery of lot from vendor to buyer is conducted under equal size shipment and the lead time is assumed to be constant. The defective items founded by the inspector in buyer side are carried in buyerâ€™s storage until the next shipment and will be returned to the vendor. The goal of the proposed model is to determine optimal delivery frequency, review period and production rate by minimizing the joint total cost. A sensitivity analysis is performed to show the impact of the changes of the decision variables on modelâ€™s behavior. The result from the sensitivity analysis shows that the joint total cost is sensitive to the changes of defect rate, demand uncertainty and demand rate.Â